The Qur’ānic Verses of Bequest and the Apparent Conflict of Texts: A Maqāṣidī Tafsīr Approach to Ta‘āruḍ al-Nuṣūṣ - Supriyadi, Imam; Ela , Rosyida (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2026)
This article examines the apparent conflict (ta‘āruḍ al-nuṣūṣ) between QS. al-Baqarah [2]:180 on wills (waṣiyyah) and QS. al-Nisā' [4]:11–12 on the provisions of a fixed inheritance share (farā’iḍ) through the perspective of maqāṣidī interpretation. Most classical commentators view the will verses as having been abrogated (mansūkh) by the inheritance verses or by the hadith “lā wasiyyata li-wārith”. At the same time, many contemporary scholars reject the concept of total abrogation and prefer to understand it as a relationship of takhṣīṣ, taqyīd, or normative harmonization. Using a hermeneutical approach based on the maqāṣid al-syarī‘ah and a semantic analysis of the wording of the verses, this article argues that the conflict perceived so far is not a substantive conflict between texts, but rather a consequence of differences in interpretation methodologies and in the meanings of linguistic elements. Therefore, the provisions of wills and inheritance are not in a mutually exclusive relationship but complement each other to achieve the objectives of sharia. This article concludes that the Qur'anic legal system regarding wills and inheritance constitutes an integrative legal-ethical unity, oriented towards the protection of property, distributive justice, social solidarity, and the balance of family relations, in accordance with the objectives of maqāṣid al-syarī‘ah.